MICROSATELLITE MARKER BASED CHARACTERIZATION AND DIVERSITY ANALYSIS OF WHEAT - SATISH KUMAR; RAJEEV KUMAR; M. Z. SHAMIM (The Bioscan, 2015)
Molecular characterization of 18 wheat cultivars and the amplification was successfully carried out 23 SSR primer pairs. A total of 341 allelic variants were detected with an average of 9.2 alleles per locus in which 226 unique alleles were observed at 37 SSR loci, with an average of 6.10 unique alleles per locus. Polymorphism information content (PIC) value ranged from 0.347 for the primer Xgwm369 to 0.858 for Xgwm251 & Xgwm282 with an average of 0.691. A maximum similarity coefficient was found between AKAW 4189-3 and Kauz/AA/ Kauz (0.93) while minimum similarity was found between PBW343 and Kauz-dwarf (0.63).The Dendrogram was constructed using Jaccard’s similarity coefficients to which entries were classified into six groups on the basis of drawing phenon line at 0.85 coefficient of similarity level. Results of this experiment indicates that hybridiza- tion between AKAW4008 with RSP561, AKAW4008 with MB4010, Kauz/AA/Kauz with RSP561, Kauz/AA/ Kauz with MB4010 will produce high yielding heat tolerant hybrid of wheat, because these parental lines has wide genetic base . The results of this experiment suggest that hybridization between AKAW4008 with C306 and Raj3765 with C306 will not produce high yielding heat tolerant hybrid of wheat, because these parental lines shows the narrow genetic base.